Marketing Strategy Analysis Using Swot And Qspm Matrix (Case Study On Guzzini Msmes) - Azzahra, Qonitah; Wahyuningtyas, Ratri; Firli, Anisah (International Journal of Science, Technology & Management, 2024)
The number of Micro, Small, and Medium Enterprises (MSMEs) participating in the marketplace continues to increase from 2020. This research aims to determine the condition of internal environmental factors (strengths and weaknesses) and external environmental factors (opportunities and threats) in Guzzini and analyze and identify the right marketing strategy to apply to Guzzini using the SWOT and QSPM methods. This research uses qualitative methods whose nature and research objectives are categorized into descriptive research. The research results based on SWOT analysis show that 6 (six) alternative strategies can be implemented, namely 1 (one) SO (Strengths-Opportunities) Strategy to seize opportunities and overcome weaknesses and face various threats, 2 (two) WO (Weaknesses-Opportunities) Strategies to Minimize the company's internal weaknesses by exploiting Guzzini's external opportunities, 2 (two) ST (Strengths-Threats) Strategies to face or reduce the impact of external threats and 1 (one) WT (Weaknesses-Threats) Strategy to deal with threats that will be faced and reduce internal weaknesses. Determining Guzzini's strategy begins with understanding the strengths and weaknesses in Guzzini's internal environment and recognizing the opportunities and threats in Guzzini's external environment. Based on the SWOT analysis, six alternative marketing strategies can be used at Guzzini. Meanwhile, based on the QSPM analysis, the most suitable strategy is to carry out more creative promotional activities and reactivate offline and online stores simultaneously.